Rock mass damage and induced passive depressurisation around open pits - A. Bloem; M. Royle; R. Uken (The Southern African Institute of Mining and Metallurgy, 2025)
Rock mass damage induced by mining increases the fracture frequency and joint aperture width in the pit walls and rock mass behind open pit mine slopes. The depth and intensity of this mechanical damage relative to the pre-mining state is not well understood and yet is a major factor in the development of slope stability models and operational guidelines. The induced damage can be partitioned into domains or zones. The blast damage zone is essentially a ‘free flow’ rock mass volume, which transitions quite rapidly into the excavation damage zone, which extends beyond that. In both zones, transient high in situ water pressures are often linked to unstable slope conditions. Whereas rock damage can enhance passive depressurisation in the rock mass, high infiltration rates on the other hand, as one could expect during rainstorm events, will decrease slope stability within the dilated pit rock mass, especially in the blast damage zone-excavation damage zone, by increasing pore pressures for short periods of time. Ice jacking and freshet are additional factors to consider in (sub) arctic environments and can be exacerbated by unfavorable rock fabric orientation. On a local scale, brittle deformation damage zones, in the form of faults, can contribute to slope instability, or enhanced stability because of slope depressurisation, depending on their location and orientation relative to the pit shape and the water sources. In this study, the shapes of the damage zones and their anticipated impact on infiltration and/or passive depressurisation are considered for different pit morphologies, rock mass conditions, in situ stress, and hydrogeological settings. Some unusual hydrological situations, like mining towards rivers and lakes and the potential effects on pore pressures, are also considered. This investigation has resulted in the development of a method to adjust initial hydraulic conductivity values used to estimate transient pore pressure conditions found in rock masses exposed in different pit morphologies and stress regimes as well as discontinuities’ orientation relative to open faces within the open pit mine. The changes in K values and pore pressures can then be used to determine hydrogeological influence more accurately on future pit slope stability.